Equivalent-circuit model that quantitatively describes domain-wall conductivity in ferroelectric lithium - Zahn, Manuel; Beyreuther, Elke; Kiseleva, Iuliia; Lotfy, Ahmed Samir; McCluskey, Conor J.; Maguire, Jesi R.; Suna, Ahmet; Rüsing, Michael; Gregg, J. Marty; Eng, Lukas M. (Physical Review Applied)
Ferroelectric domain wall (DW) conductivity (DWC) can be attributed to two separate mechanisms: (a) the injection/ejection of charge carriers across the Schottky barrier formed at the (metal-)electrode-DW junction and (b) the transport of those charge carriers along the DW. Current-voltage (I-U) characteristics, recorded at variable temperatures from LiNbO3 (LNO) DWs, are clearly able to differentiate between these two contributions. Practically, they allow us to directly quantify the physical parameters relevant to the two mechanisms (a) and (b) mentioned above. These are, for example, the resistance of the DW, the saturation current, the ideality factor, and the Schottky barrier height of the electrode-DW junction. Furthermore, the activation energies needed to initiate the thermally activated electronic transport along the DWs can be extracted. In addition, we show that electronic transport along LNO DWs can be elegantly viewed and interpreted in an adapted semiconductor picture based on a double-diode, double-resistor equivalent-circuit model, the R2D2 model. Finally, our R2D2 model was checked for its universality by successfully fitting the I-U curves of not only z-cut LNO bulk DWs, but equally of z-cut thin-film LNO DWs, and of x-cut thin-film DWs as reported in literature.
Keywords: General Physics and Astronomy

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Decomposing large unitaries into multimode devices of arbitrary size - Arends, Christian; Wolf, Lasse Lennart; Meinecke, Jasmin; Barkhofen, Sonja; Weich, Tobias; Bartley, Tim (Physical Review Research)
Keywords: General Physics and Astronomy

Tailored Frequency Conversion Makes Infrared Light Visible for Streak Cameras - Lüders, Carolin; Gil-Lopez, Jano; Allgaier, Markus; Brecht, Benjamin; Aßmann, Marc; Silberhorn, Christine; Bayer, Manfred (Physical Review Applied)
Keywords: General Physics and Astronomy

Circularly polarized electroluminescence from a single-crystal organic microcavity light-emitting diode based on photonic spin-orbit interactions - Jia, Jichao; Cao, Xue; Ma, Xuekai; De, Jianbo; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Realization of a Multi-Output Quantum Pulse Gate for Decoding High-Dimensional Temporal Modes of Single-Photon States - Serino, Laura; Gil López, Jano; Stefszky, Michael; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
Keywords: General Physics and Astronomy; Mathematical Physics; Applied Mathematics; Electronic; Optical and Magnetic Materials; Electrical and Electronic Engineering; General Computer Science

Tracking Quantum Coherence in Polariton Condensates with Time-Resolved Tomography - Lüders, Carolin; Pukrop, Matthias; Barkhausen, Franziska; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Physical Review Letters)
Keywords: General Physics and Astronomy

Revealing the nonadiabatic tunneling dynamics in solid-state high harmonic generation - Zuo, Ruixin; Song, Xiaohong; Ben, Shuai; Meier, Torsten; Yang, Weifeng (Physical Review Research)
Keywords: General Physics and Astronomy

Manipulation of nonautonomous nonlinear wave solutions of the generalized coupled Gross–Pitaevskii equations with spin–orbit interaction and weak Raman couplings - Belobo, D. Belobo; Meier, Torsten (Results in Physics)
Keywords: General Physics and Astronomy

Dynamic control of hybrid grafted perfect vector vortex beams - Ahmed, Hammad; Ansari, Muhammad Afnan; Li, Yan; Zentgraf, Thomas; Mehmood, Muhammad Qasim; Chen, Xianzhong (Nature Communications)
Perfect vector vortex beams (PVVBs) have attracted considerable interest due to their peculiar optical features. PVVBs are typically generated through the superposition of perfect vortex beams, which suffer from the limited number of topological charges (TCs). Furthermore, dynamic control of PVVBs is desirable and has not been reported. We propose and experimentally demonstrate hybrid grafted perfect vector vortex beams (GPVVBs) and their dynamic control. Hybrid GPVVBs are generated through the superposition of grafted perfect vortex beams with a multifunctional metasurface. The generated hybrid GPVVBs possess spatially variant rates of polarization change due to the involvement of more TCs. Each hybrid GPVVB includes different GPVVBs in the same beam, adding more design flexibility. Moreover, these beams are dynamically controlled with a rotating half waveplate. The generated dynamic GPVVBs may find applications in the fields where dynamic control is in high demand, including optical encryption, dense data communication, and multiple particle manipulation.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Telecom C-band photon emission from (In,Ga)As quantum dots generated by filling nanoholes in In0.52Al0.48As layers - Deutsch, D.; Buchholz, C.; Zolatanosha, V.; Jöns, K. D.; Reuter, D. (AIP Advances)
We present the fabrication of strain-free quantum dots in the In0.53Ga0.47As/In0.52Al0.48As-system lattice matched to InP, as future sources for single and entangled photons for long-haul fiber-based quantum communication in the optical C-band. We achieved these quantum dots by local droplet etching via InAl droplets in an In0.52Al0.48As layer and subsequent filling of the holes with In0.53Ga0.47As. Here, we present detailed investigations of the hole morphologies measured by atomic force microscopy. Statistical analysis of a set of nanoholes reveals a high degree of symmetry for nearly half of them when etched at optimized temperatures. Overgrowth with 50–150 nm In0.52Al0.48As increases their diameter and elongates the holes along the [01̄1]-direction. By systematically scanning the parameter space, we were able to fill the holes with In0.53Ga0.47As, and by capping the filled holes and performing photoluminescence measurements, we observe photoluminescence emission in the O-band up into the C-band depending on the filling height of the nanoholes.
Keywords: General Physics and Astronomy

Modeling nonlinear optical interactions of focused beams in bulk crystals and thin films: A phenomenological approach - Spychala, Kai J.; Amber, Zeeshan H.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Coherent nonlinear optical μ-spectroscopy is a frequently used tool in modern material science as it is sensitive to many different local observables, which comprise, among others, crystal symmetry and vibrational properties. The richness in information, however, may come with challenges in data interpretation, as one has to disentangle the many different effects like multiple reflections, phase jumps at interfaces, or the influence of the Guoy-phase. In order to facilitate interpretation, the work presented here proposes an easy-to-use semi-analytical modeling Ansatz, which bases upon known analytical solutions using Gaussian beams. Specifically, we apply this Ansatz to compute nonlinear optical responses of (thin film) optical materials. We try to conserve the meaning of intuitive parameters like the Gouy-phase and the nonlinear coherent interaction length. In particular, the concept of coherence length is extended, which is a must when using focal beams. The model is subsequently applied to exemplary cases of second- and third-harmonic generation. We observe a very good agreement with experimental data, and furthermore, despite the constraints and limits of the analytical Ansatz, our model performs similarly well as when using more rigorous simulations. However, it outperforms the latter in terms of computational power, requiring more than three orders less computational time and less performant computer systems.
Keywords: General Physics and Astronomy

Time-resolved pump–probe spectroscopic ellipsometry of cubic GaN. I. Determination of the dielectric function - Baron, Elias; Goldhahn, Rüdiger; Espinoza, Shirly; Zahradník, Martin; Rebarz, Mateusz; Andreasson, Jakob; Deppe, Michael; As, Donat Josef; Feneberg, Martin (Journal of Applied Physics)
An ultra-fast change of the absorption onset for zincblende gallium-nitride (zb-GaN) (fundamental bandgap: 3.23 eV) is observed by investigating the imaginary part of the dielectric function using time-dependent femtosecond pump–probe spectroscopic ellipsometry between 2.9 and 3.7 eV. The 266 nm (4.66 eV) pump pulses induce a large electron–hole pair concentration up to 4×1020cm−3, which shift the transition energy between conduction and valence bands due to many-body effects up to ≈500 meV. Here, the absorption onset increases due to band filling while the bandgap renormalization at the same time decreases the bandgap. Additionally, the absorption of the pump-beam creates a free-carrier profile within the 605 nm zb-GaN layer with high free-carrier concentrations at the surface, and low concentrations at the interface to the substrate. This leads to varying optical properties from the sample surface (high transition energy) to substrate (low transition energy), which are taken into account by grading analysis for an accurate description of the experimental data. For this, a model describing the time- and position-dependent free-carrier concentration is formulated by considering the relaxation, recombination, and diffusion of those carriers. We provide a quantitative analysis of optical experimental data (ellipsometric angles Ψ and Δ) as well as a plot for the time-dependent change of the imaginary part of the dielectric function.
Keywords: General Physics and Astronomy

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Threshold photoelectron spectroscopy and dissociative photoionization of benzonitrile - Kamer, Jerry; Schleier, Domenik; Donker, Merel; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy (Physical Chemistry Chemical Physics)
The seven parallel dissociative ionization channels of benzonitrile yield highly stable fragment ions with commensurate abundance, underlining the potential role of the benzonitrile cation as hub species in the interstellar medium.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, D.; Meier, T.; Sharapova, P. R. (Physical Review Research)
Keywords: General Physics and Astronomy

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, Dennis; Meier, T.; Sharapova, P. R. (Physical Review Research)
Keywords: General Physics and Astronomy

Hall mobilities and sheet carrier densities in a single LiNbO3 conductive ferroelectric domain wall - Beccard, Henrik; Beyreuther, Elke; Kirbus, Benjamin; Seddon, Samuel D.; Rüsing, Michael; Eng, Lukas M. (Physical Review Applied)
In the last decade, conductive domain walls (CDWs) in single crystals of the uniaxial model ferroelectric lithium niobate (LiNbO3; LNO) have been shown to reach resistances more than 10 orders of magnitude lower than the resistance of the surrounding bulk, with charge carriers being firmly confined to sheets with a width of a few nanometers. LNO is thus currently witnessing increased attention because of its potential in the design of room-temperature nanoelectronic circuits and devices based on such CDWs. In this context, the reliable determination of the fundamental transport parameters of LNO CDWs, in particular the 2D charge carrier density n2D and the Hall mobility μH of the majority carriers, is of great interest. In this contribution, we present and apply a robust and easy-to-prepare Hall-effect measurement setup by adapting the standard four-probe van der Pauw method to contact a single, hexagonally shaped domain wall that fully penetrates the 200-μm-thick LNO bulk single crystal. We then determine n2D and μH for a set of external magnetic fields B and prove the expected cosinelike angular dependence of the Hall voltage. Lastly, we present photoinduced-Hall-effect measurements of one and the same DW, by determining the impact of super-band-gap illumination on n2D.
Keywords: General Physics and Astronomy

Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Ali, Usman; Holthaus, Martin; Meier, Torsten (Physical Review Research)
Keywords: General Physics and Astronomy

Resonance enhanced multiphoton ionization detection of aromatics formation in fuel-rich flames - Kasper, Tina; Hansen, Nils (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry